2010
DOI: 10.1144/0070369
|View full text |Cite
|
Sign up to set email alerts
|

The Buzzard Field: anatomy of the reservoir from appraisal to production

Abstract: The Buzzard oil field in the Outer Moray Firth, Central North Sea was discovered in 2001 and rapidly appraised during [2001][2002]. Pre-production development drilling began in 2005 and the field was brought on stream in January 2007 by operator Nexen Petroleum UK Ltd. The Buzzard reservoir consists of Upper Jurassic deep marine turbidites within the Kimmeridge Clay Formation. Sands were derived from the shelf to the west and the resulting mass flow deposits were contained within a fault-bounded basin, whose m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…If sandy deposits downstream of a slope break are connected to the updip slope sands, potential hydrocarbons leak through those connections. In contrast, a system with slope-detached sand sedimentation may result in the formation of sealed reservoirs (Doré and Robbins, 2005;Ray et al, 2010). The estimation of the bypass-slope criterion and the comparison with the actual upper slope in a slope-break system provides a rough assessment of the likelihood of whether or not deposits drape the upper slope.…”
Section: Stratigraphic Development Of Slope-break Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…If sandy deposits downstream of a slope break are connected to the updip slope sands, potential hydrocarbons leak through those connections. In contrast, a system with slope-detached sand sedimentation may result in the formation of sealed reservoirs (Doré and Robbins, 2005;Ray et al, 2010). The estimation of the bypass-slope criterion and the comparison with the actual upper slope in a slope-break system provides a rough assessment of the likelihood of whether or not deposits drape the upper slope.…”
Section: Stratigraphic Development Of Slope-break Systemsmentioning
confidence: 99%
“…Sediment deposits in slope-break systems can serve as potential reservoirs for hydrocarbons (Pettingill, 2004;Weimer and Slatt, 2004;Zou et al, 2015). The likelihood of forming a sealed reservoir depends on the proximal termination point of the sediment bodies, like those seen in the Buzzard Field (Doré and Robbins, 2005;Ray et al, 2010). The location of the point where the current transitions from bypass to depositional conditions is here termed up-dip pinch-out (UDPO).…”
Section: Introductionmentioning
confidence: 99%
“…STOIIP estimate is 1.4BBO, making it a world-class giant field discovery (Ray et al 2010). The trap is a combination of fault closures on the north and south and stratigraphic closure to the west.…”
Section: Case History 5: Buzzard Field United Kingdom Missing a Keymentioning
confidence: 99%
“…One of the largest discoveries globally made in the last 15 years was that of the Buzzard Field in the North Sea (Carstens 2005;Ray et al 2010;Robbins and Dore 2005). The prospective acreage block was acquired by Amoco in the late 1995, in partnership with British Gas.…”
Section: Case History 5: Buzzard Field United Kingdom Missing a Keymentioning
confidence: 99%
“…In the Upper Jurassic turbidites of the Buzzard Field, North Sea, stratigraphic compartmentalization was identified shortly after production began by pressure-time analyses of pressure monitoring wells adjacent to a production well (Ray et al 2010). These data showed that, after water injection began, pressure declined in three wells but increased in a fourth.…”
Section: Recognition Of Stratigraphic Compartmentalizationmentioning
confidence: 99%